A phenomenological study of Malaysian counsellors’ experiences in managing countertransference - Lee, Wei Lu; Lau, Poh Li; Baranovich, Diana Lea; Chan, Siaw Leng (Springer Nature, 2022)
Processing and managing countertransference are part of the responsibilities of counsellors to fulfil their ethical obligation. The transcendental phenomenological design was applied in the present study to examine the subjective lived experiences of counsellors in managing their countertransference. The data of six Malaysian counsellors who reported experiencing countertransference were collected through audio recordings and in-depth phenomenological interviews. The collected data were analysed using Moustakas’ data analysis method. Seven themes emerged from the study: self-reflection, professional consultation, recognising the occurrence of countertransference; personal self-care strategies; emotion regulation; preparation for cases; and physical and emotional separation. Each major theme was supported by subthemes. This study highlighted the effective ways for counsellors in managing their countertransference experiences throughout their professional helping journey.